2020
DOI: 10.1136/rapm-2020-102088
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous auricular vagus nerve stimulation (taVNS) for migraine: an fMRI study

Abstract: BackgroundDysfunction of the thalamocortical connectivity network is thought to underlie the pathophysiology of the migraine. This current study aimed to explore the thalamocortical connectivity changes during 4 weeks of continuous transcutaneous vagus nerve stimulation (taVNS) treatment on migraine patients.Methods70 migraine patients were recruited and randomized in an equal ratio to receive real taVNS or sham taVNS treatments for 4 weeks. Resting-state functional MRI was collected before and after treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
76
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 51 publications
4
76
0
5
Order By: Relevance
“…In our previous published article (Zhang et al, 2021) Episodic migraineurs without aura were diagnosed by licensed neurologists according to the 2nd Edition International Classification of Headache Disorders for Migraine Without Aura (Headache Classification Subcommittee of the International Headache Society, 2004). The detailed inclusion criteria for the MWoA patients are as follows: (1) aged 18-45 years old, (2) righthanded, (3) have at least 6 months of migraine duration, (4) have at least two headache attacks per month, (5) have not taken any prophylactic headache medications during the past 1 month, and (6) have not taken any psychoactive or vasoactive drugs during the past 3 months.…”
Section: Participantsmentioning
confidence: 99%
“…In our previous published article (Zhang et al, 2021) Episodic migraineurs without aura were diagnosed by licensed neurologists according to the 2nd Edition International Classification of Headache Disorders for Migraine Without Aura (Headache Classification Subcommittee of the International Headache Society, 2004). The detailed inclusion criteria for the MWoA patients are as follows: (1) aged 18-45 years old, (2) righthanded, (3) have at least 6 months of migraine duration, (4) have at least two headache attacks per month, (5) have not taken any prophylactic headache medications during the past 1 month, and (6) have not taken any psychoactive or vasoactive drugs during the past 3 months.…”
Section: Participantsmentioning
confidence: 99%
“…Additional taVNS studies highlight increased neural activity or altered BOLD responses within the locus coeruleus 36,37,[42][43][44][45] , which is a major target of adrenergic influences that has bidirectional communication with the NST 46 . taVNS moreover elicits BOLD responses within the insula, ACC, OFC, hypothalamus, thalamus, and amygdala 36,39,44,[47][48][49] .…”
mentioning
confidence: 99%
“…We found migraine is associated with altered posterior thalamus dynamic network functional connectivity with the visual cortex [ 79 ], and the abnormal functional connectivity within the visual, default mode, sensorimotor, and frontal-parietal networks, which could discriminate migraineurs from healthy controls, with 93% sensitivity and 89% specificity [ 95 ]. More recently, we found that 4-week taVNS at 1 Hz can decrease the connectivity between the occipital cortex-related thalamus subregion and the postcentral gyrus/precuneus [ 96 ]. Taken together, these studies demonstrate the important role of the precuneus and cuneus in the pathology of migraine.…”
Section: Discussionmentioning
confidence: 99%